Metformin Ameliorates Uterine Defects in a Rat Model of Polycystic Ovary Syndrome - Zhang, Yuehui (EBioMedicine, 2017)
Adult rats treated concomitantly with insulin and human chorionic gonadotropin exhibit endocrine, metabolic, and reproductive abnormalities that are very similar to those observed in polycystic ovary syndrome (PCOS) patients. In this study, we used this rat model to assess the effects of metformin on PCOS-related uterine dysfunction. In addition to reducing androgen levels, improving insulin sensitivity, and correcting the reproductive cycle, metformin treatment induced morphological changes in the PCOS-like uterus. At the molecular and cellular levels, metformin normalized the androgen receptor-mediated transcriptional program and restored epithelial–stromal interactions. In contrast to glucose transport, uterine inflammatory gene expression was suppressed through the PI3K–Akt–NFκB network, but without affecting apoptosis. These effects appeared to be independent of AMPK subunit and autophagy-related protein regulation. We found that when metformin treatment partially restored implantation, several implantation-related genes were normalized in the PCOS-like rat uterus. These results improve our understanding of how metformin rescues the disruption of the implantation process due to the uterine defects that result from hyperandrogenism and insulin resistance. Our data provide insights into the molecular and functional clues that might help explain, at least in part, the potential therapeutic options of metformin in PCOS patients with uterine dysfunction.